Ethnic-Based Deprivation and Its Impacts on Political Instability in Khyber Pakhtunkhwa, Pakistan - Farhad Ali; Ifra Zaheer; Attaullah Veesar (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines the relationship between ethnic-based deprivation and political instability in Khyber Pakhtunkhwa, Pakistan, using a quantitative approach. A sample of 296 individuals was selected from a population of 1280, and data was collected through a structured questionnaire. The results, presented in tables, reveal a significant link between ethnic-based deprivation and political instability. Economic exclusion, political marginalization, and social inequality are identified as key factors perpetuating deprivation and instability. The findings emphasize the need to address ethnic disparities to promote peace and stability in the region. This research provides valuable insights for policymakers and stakeholders working to address ethnic tensions and promote inclusive development in Khyber Pakhtunkhwa. By understanding the complex dynamics of ethnic-based deprivation and political instability, this study aims to inform evidence-based policies that promote a more equitable and stable future for the region. The findings of this study have important implications for promoting social cohesion, reducing inequality, and improving political stability in Khyber Pakhtunkhwa.